Microstructural analysis to uniaxial low cyclic compression of high-strength concrete after high temperature. Issue 3 (February 2019) - Zhao, Dongfu; Jia, Penghe; Hou, Pingying; Liu, Huixuan; Zhao, Rundong; Gao, Haijing
The uniaxial compressive cycling tests of high-strength concrete after high temperature under different stress were carried out using the electrohydraulic servo-controlled fatigue testing system. The investigation focused on low-cycle fatigue to figure out the relationship between microstructural development and number of cycles. The variation in microstructure during uniaxial compressive fatigue process was systematically analyzed and compared using ultrasonic, micro-hardness test, mercury intrusion porosimetry, and scanning electron microscopy. It is found that at the same life ratio, the cumulative fatigue damage caused by the lower stress is greater than that caused by the higher stress, and the four kinds of test methods used to measure the microstructure are consistent, interrelated, and confirmed with each other well. Through the nonlinear regression analysis of fatigue residual strain and microstructural parameters, the relationship models between them were established. Furthermore, the fatigue damage models based on microstructural parameters were established. On this basis, both the dynamic evolution process and damage mechanism of microstructure during uniaxial compressive fatigue were further revealed.